Optimal control of a reverse osmosis desalination plant using multi-objective optimization - Gambier, Adrián; Wellenreuther, Andrea; Badreddin, Essameddin (IEEE International Symposium on Computer-Aided Control Systems Design, 2006, 2006)
In this contribution, the control of a reverse osmosis desalination plant by using an optimal multi-loop approach is presented. Controllers are assumed to be players of a cooperative game, whose solution is obtained by multi-objective optimization (MOO). The MOO problem is solved by applying a genetic algorithm and the final solution is found from this Pareto set. For the reverse osmosis plant a control scheme consisting of two PI control loops are proposed. Simulation results show that in some cases, as for example this desalination plant, multi-loop control with several controllers, which have been obtained by join multi-objective optimization, perform as good as more complex controllers but with less implementation effort.